Identificación cromatográfica de Benzoilecgonina en orina de personas detenidas en el Complejo Policial de Trujillo, mayo – julio 2017 - Angulo Díaz, Diana Carolina (2019)
The objective of this report was to identify Benzoylecgonine by thin layer chromatography (TLC) in urine of people detained in the Cap. PNP. Alcides Vigo Hurtado de Trujillo, during the months of May to July 2017; the highest percentage was determined according to sex, age range, place of police origin; for this, a total of 552 urine samples obtained in the weighing area of said institution were used, after being lacquered and labeled they were transferred to the laboratory for the respective analysis. Among the results obtained, 24.09% of the samples were positive, of which 98.5% correspond to men, consumption is higher in men than in women, 53.38% are included in the 18 to 29 years and 37.59% come from the district of La Esperanza